Determination of respiratory syncytial virus epidemic seasons by using 95% confidence interval of positivity rates, 2011–2021, Germany. Issue 5 (29th April 2022) - Cai, Wei; Dürrwald, Ralf; Biere, Barbara; Schweiger, Brunhilde; Haas, Walter; Wolff, Thorsten; Buda, Silke; Reiche, Janine
Abstract: Based on our national outpatient sentinel surveillance, we have developed a novel approach to determine respiratory syncytial virus (RSV) epidemic seasons in Germany by using RSV positivity rate and its lower limit of 95% confidence interval. This method was evaluated retrospectively on nine RSV seasons, and it is also well‐suited to describe off‐season circulation of RSV in near real time as observed for seasons 2020/21 and 2021/22 during the COVID‐19 pandemic. Prospective application is of crucial importance to enable timely actions for health service delivery and prevention.